Selección de leguminosas forrajeras e inoculación con Rhizobium en dos localidades de la zona cafetera - Suárez Vásquez, Senén; Wood, Martin; Nortcliff, Stephen (1991)
At the Colombian coffee growing area, between 1,000 and 2,000m elevation, experiments were carried out under field conditions on steep slopes at Romelia (2,500 mm rainfall and a Dystrandept type of soil), and at Supía (1,708 mm rainfall and a Eutrandept type of soil). The legumes (Centrosema macrocarpum CIAT 5065, Centrosema pubescens CIAT 438, Pueraria phaseoloides CIAT 9900, Arachis pintoi CIAT 17434, Desmodium ovalifolium CIAT 350 and Leucaena leucocephala CIAT 17481) were established either alone or in combination with the grass Brachiaria decumbens, using minimum soil disturbance. Arachis pintoi was the best legume in terms of soil cover and dry matter production. Arachis pintoi sown by seed or vegetative propagation and Desmodium ovalifolium planted vegetatively could be sown directly among either native or introduced grasses without seed bed preparation. Weeding by herbicide was necessary when introducing legumes into existing Paspalum pasture, but was not necessary among introduced Brachiaria decumbens which leaves spaces among plants. Legume dry matter production and ground cover were similar when grown as pure stand and in mixture with B. decumbens (both planted in the same site). No inoculation response was found for most of the legumes except Centrosema macrocarpum CIAT 5065 inoculated with Rhizobumm strain CIAT 3101. The establishment time under these conditions was three months. The establishment of legumes other than Arachis pintoi was slower and needed more weeding, increasing cost and the risk of soil erosion. Desmodium ovalifolium and Leucaena leucocephala could not be established by seed directly in the field due to their low competitive abilities against native grasses